Inhibition of polyamine biosynthesis for toxicity control in Serratia marcescens strain WW4 by targeting ornithine decarboxylase: a structure-based virtual screening study. (2018) - Dhusia, Kalyani; Yadav, Pramod K.; Farmer, Rohit; Ramteke, Pramod W.
Ornithine decarboxylase (ODC) enzyme, catalyses the decarboxylation of ornithine to form spermidine which is a committed step in the biosynthesis of polyamines. Here, in the present work, structure of ODC was modelled and studied for its active site. The stability of modelled structure was revalidated by the molecular dynamics simulation at 50 nano second time scale. 142 Natural products of Indofine Herbal Ingredient library from ZINC database were screened using Autodock Vina for the identification of potential leading herbal inhibitors. The results obtained from docking showed that Conessine is best inhibiting candidate with docking affinity of –9.7 Kcal/mol. Conessine is an alkaloid which proves its immense importance as metabolites. Thus, polyamine being harmful when synthesised in excess are necessary to be controlled at their genesis. Therefore, conessine might be a potential inhibitor for toxicity control in plant growth promoting rhizobacteria.